Antennae-enriched expression of candidate odorant degrading enzyme genes in the turnip aphid, Lipaphis erysimi - Shangguan, Chaozhi; Kuang, Yinhui; Gao, Liwei; Zhu, Bo; Chen, Xue Dong; Yu, Xiudao (Frontiers in Physiology, 2023)
Aphids heavily rely on their olfactory system for foraging behavior. Odorant-degrading enzymes (ODEs) are essential in preserving the olfactory acuity of aphids by removing redundant odorants in the antennae. Certain enzymes within this group stand out as being enriched and/or biased expressed in the antennae, such as carboxylesterases (CXEs), cytochrome P450 (CYPs), glutathione S-transferases (GSTs), and UDP-glycosyltransferases (UGTs). Here, we performed a comparative transcriptome analysis of antennae and body tissue to isolate the antennal ODE genes of turnip aphid Lipaphis erysimi. A dataset of one CXE, seven CYPs, two GSTs, and five UGTs enriched in the antennae was identified and subjected to sequence analysis. Furthermore, qRT-PCR analyses showed that 13 ODE genes (LeCXE6, LeCYP4c1, LeCYP6a2, LeCYP6a13, LeCYP6a14.2, LeCYP6k1, LeCYP18a1, LeGST1, LeUGT1-7, LeUGT2B7, LeUGT2B13, LeUGT2C1.1, and LeUGT2C1.2) were specifically or significantly elevated in antennal tissues. Among these antennae-enriched ODEs, LeCYP4c1, LeCYP6a2, LeCYP6a13, LeCYP6a14.2, LeCYP18a1, LeUGT2B7, and LeUGT2B13 were found to exhibit significantly higher expression levels in alate aphids compared to apterous and nymph aphids, suggesting their putative role in detecting new host plant location. The results presented in this study highlight the identification and expression of ODE genes in L. erysimi, paving the path to investigate their functional role in odorant degradation during the olfactory processes.